DOI: 10.33915/etd.5696
|View full text |Cite
|
Sign up to set email alerts
|

Clustering By Academic Major at Historically Black Colleges and Universities (HBCUs)

Abstract: Clustering By Academic Major at Historically Black Colleges and Universities (HBCUs) Aaron Goodson Follow-up studies of clustering by academic major, the dynamic of 25% or more of the studentathletes on a roster pursuing the same academic major, indicate that it still occurs in revenuegenerating sports (Fountain & Finley 2009, 2011; Otto, 2012). Clustering challenges the notion that student-athletes have control over their collegiate academic experience and reveals that their educational pursuits may not align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Teachers may instead allocate a large amount of time to what has been described as "vigorous arguments" on the topic under consideration. As a result of the current issue-based challenge, the ideological and political courses in high school are being driven to reassess their activity-based curriculum [11]. If students get issue-based training, such as that espoused by DL, it is possible that they will profit.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers may instead allocate a large amount of time to what has been described as "vigorous arguments" on the topic under consideration. As a result of the current issue-based challenge, the ideological and political courses in high school are being driven to reassess their activity-based curriculum [11]. If students get issue-based training, such as that espoused by DL, it is possible that they will profit.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found evidence of academic clustering among NCAA Division I football programs, especially at the "Power Five" level (Fountain & Finley, 2009;Houston & Baber, 2017;Otto, 2012;Watkins & Slater, 2021), although it occurs to a lesser extent at the FCS level (Paule-Koba, 2020). In addition to football, some men's and women's NCAA Division I basketball and baseball programs also academically cluster (Case et al, 1987;Goodson, 2015;Miller, 2021;Paule-Koba, 2015).…”
Section: Academic Clusteringmentioning
confidence: 99%
“…Multiple studies have determined that black, male, and "high profile" sport college athletes were more likely to be in a clustered major (Case et al, 1987;Fountain & Finley, 2009;Sanders & Hildenbrand, 2010;Houston & Baber, 2017), although another found that minority college athletes did not academically cluster more frequently at the FCS level (Paule-Koba, 2020). Research shows that while academic clustering takes place among men's NCAA Division I basketball teams (Case et al, 1987), it is less common among NCAA Division I women's teams and historically black college and university (HBCU) basketball programs (Goodson, 2015;Paule-Koba, 2015). The academic clustering of "Power Five" football programs also appears more prevalent among institutions with higher admissions standards (Love et al, 2017).…”
Section: Academic Clusteringmentioning
confidence: 99%